Organizational barriers to absorptive capacity building for international technology transfer to Malaysia - Van Der Heiden, P. (Institute of Electrical and Electronics Engineers Inc., 2016)
International technology transfer and absorptive capacity play a trivial role in technological capacity building in newly industrialized countries. Despite various ambitious and visionary roadmaps, Malaysia's aerospace industry is still confined to basic manufacturing, maintenance, repair and overhaul and lacks substantial research and development and design activities. As absorptive capacity is a prerequisite for organizational learning, which is the basis for technological capacity building, identifying barriers to absorptive capacity building is essential to explain why Malaysia is performing suboptimal in realizing technological capacity building in the aerospace realm. A questionnaire survey and in-depth one-on-one semi-structured interviews utilizing the Delphi survey method with respondents in the global, Southeast Asian and Malaysian aerospace sectors were executed. Data triangulation of the questionnaire and Delphi survey was applied. The generated data was statistically analyzed and the extracted results identified the prevalence of various organizational barriers to absorptive capacity in the Malaysian aerospace industry. This empirical research further contributes to the extant literature on absorptive capacity. The results carry significant implications for policy-makers, managers, professionals and academics in the field of international technology transfer and absorptive capacity.